From cellular microbiology to bacteria‐based next generations of cancer immunotherapies. (17th March 2020) - Osuna‐Pérez, Jesús; García‐Ferreras, Raquel; Veiga, Esteban
Abstract: Pioneer work by Prof. Cossart among others, studying the interactions between pathogenic bacteria and host cells (this discipline was termed Cellular Microbiology), was fundamental to determine the bacterial infection processes and to improve our knowledge of different cellular mechanisms. The study of bacteria–host interactions also involves in vivo host immune responses, which can be manipulated by bacteria, being these last potent tools for different immunotherapies. During the last years, tumour immunotherapies, mainly the use of antibodies that target immune checkpoints [checkpoint inhibitors (CPI)], have been a revolution in oncology, allowing the treatment of tumours otherwise with very bad prognosis. In the same direction, bacteria inoculations have been used from long to treat some cancers; for example, non‐muscle‐invasive bladder cancer can be successfully treated with the bacterium Bacillus Calmette Guerin (BCG). More recently, it has been shown that microbiota could determine the success of CPI immunotherapies and intense research is being performed in order to use bacteria as immunotherapy tools due to their ability to activate the immune system. In this context, to expand the knowledge of the bacteria–immune system interactions will be fundamental to improve tumour immunotherapies.